STUDI EKOLOGI OSEANOGRAFI TELUK MANADO UNTUK PENENTUAN STRUKTUR ARTIFICIAL CORAL GARDEN DAN AREA MANGROVE SEBAGAI DESTINASI WISATA BARU - Oktavianus Lintong; Dannie R S Oroh; Easter Ch. M. Tulung (Sam Ratulangi University, 2019)
The purpose of this study is to investigate the ecological conditions of mangrove ecosystems in the Manado Bay and analyze the suitability of the mangrove ecosystems as a new tourist destination, examine the oceanographic conditions in the Manado Bay area, study the data on the development of coral reef ecosystems to be able to produce artificial coral reefs and produce mangrove areas and coral reefs artificial as a new tourist destination. This research was conducted in April - September 2019 with the location of Manado Bay and the location of the Manado Bay coral reef ecosystem survey set at 3 sample points, equipped with 3 points in front of the BOBOCA Malalayang monument, in front of the Malalayang gas station and ANTRA Sario. Retrieval of coral reef data is by using the Line Intercept Transect (LIT) method. LIT observations were carried out with SCUBA diving at a depth of 6m. Observations were made by recording coral lifeforms found along the transect line, and calculating the percentage of the selection. The data taken is the percentage of dead coral cover, live coral, and type of life form, diversity index taken at 3 sample points. From field observations found on Site 2 (Front of Malalayang gas station) the condition of coral reefs is included in the good category, with the percentage of live coral cover (Hard Coral) of 55%. At this station found various types of coral growth, but the highest at this station is a form of growth of Coral Masive (CM) of 19.2%, while the least found were corals in the form of Coral Mushrooms (Mushroom Coral) with a percentage of 0.4 %. Then Site 3, namely in ANTRA Sario obtained from coral reefs is included in the bad category, with the percentage of live coral cover (Hard Coral) only 7.1%. Coral Diversity in the three survey stations is different. Of the three stations determined above the Tugu Boboca Malalayang site with an index value of 2.54, followed at site 2 namely the Malalayang gas station with an index value of 2.36 and the lowest at site 3 at ANTRA Sario with an index value of 1.33. Furthermore, oceanographic conditions in the Gulf of Manado region are seen in the receding period, most of the air moves westward at the beginning of the period, then moves northeastward in the next period. While in the tide period the water moves northward, starting the period and then it is seen moving northeast and at the end of the period, the east direction.Key words : Coral reef, Oceanographic condition